Meaning and Significance of “Alkalization Therapy for Cancer” - Wada, Hiromi; Hamaguchi, Reo; Narui, Ryoko; Morikawa, Hiromasa (Frontiers in Oncology, 2022)
Objectives of the study: Our research aims to answer the following questions. Can cancer progression be stopped by changing the body condition of person with cancer?　Can cancer be cured?　If cancer progression can be stopped, what is the underlying mechanism? Theoretical rationale for alkalization therapy: Almost 70 years ago, Goldblatt H. & Cameron G. (1953) reported on the idea of alkalization therapy. Before that, Otto Warburg had been studying the metabolism of cancer and had discovered the essential nature of cancer. He published a review in Science in 1956 under the title “On the origin of cancer cells”. From his phenomena described above, we established the theoretical rationale for alkalization therapy, based on the question of “How does cancer form and what is its nature?” Limitations of deductive methods and inductive approaches: In this paper, we describe a method to reconstruct the limitations and weaknesses of modern cancer medicine as Science-based Medicine using an inductive method, and to present a new vision of cancer therapy. How should we treat cancer? (Case presentation): Using a specific clinical case, we present patients in whom were successfully treated with no or few anticancer drugs. Summary: The biggest weakness of current cancer treatments is that they only treat the cancer and not the actual patient. The “alkalization therapy” that we advocate does not compete with any of the current standard treatments, but improves the effectiveness of standard treatments, reduces side effects, and lowers medical costs.